Bacterial Teaching Material Supplement Based on the Study of Identification of Resistant Bacteria in Leachate at TPA Talumelito as a Virtual Laboratory-Based Digital Learning Resource - Siti Ainun Mabuia; Wirnangsi D. Uno; Yuliana Retnowati; Ani M. Hasan; Syam S. Kumaji; Lilan Dama (Jurnal Penelitian Pendidikan IPA, 2024)
Differentiated learning is the core of the independent curriculum now.The aim of this research is to develop an instrument for measuring the cognitive learning outcomes of high school students based on differentiated learning on elasticity material and to obtainits characteristics. Differentiation, in this case, is differentiation of student learning styles. The instrument grid is arranged based on indicators of cognitive learning outcomes, which are then used to compile question items. The test instrument consists of two test sets, each of which has 9 items including two anchor itemsso that the total number of items is 16 items and has been validated by 6 experts. The validated instrument was tested on 252 respondents spread across high schools in the low, medium and high categories. Dichotomous data were analyzed using the Partial Credit Model (PCM). The trial results showed that all 16 items and the differentiated learning-based student cognitive learning outcomes test instrument were proven to be valid, fit the PCM model, and reliable, which means all items were in the good category. Thus, the test instrument developed meets the requirements for measuring the cognitive learning outcomes of high school students on elasticity material based on differentiated learning.